In vitro and in vivo pharmacological characterization of the synthetic opioid MT-45. (July 2020) - Bilel, S; Azevedo, NJ; Arfè, R; Tirri, M; Gregori, A; Serpelloni, G; De-Giorgio, F; Frisoni, P; Neri, M; Calò, G; Marti, M
Abstract: MT-45 is a synthetic opioid that was developed in the 1970s as an analgesic compound. However, in recent years MT-45 has been associated with multiple deaths in Europe and has been included in the class of novel psychoactive substances known as novel synthetic opioids (NSOs). Little is known about the pharmaco-toxicological effects of MT-45. Therefore, we used a dynamic mass redistribution (DMR) assay to investigate the pharmacodynamic profile of this NSO in vitro compared with morphine. We then used in vivo studies to investigate the effect of the acute systemic administration of MT-45 (0.01–15 mg/kg i.p.) on motor and sensorimotor (visual, acoustic and tactile) responses, mechanical and thermal analgesia, muscle strength and body temperature in CD-1 male mice. Higher doses of MT-45 (6–30 mg/kg i.p.) were used to investigate cardiorespiratory changes (heart rate, respiratory rate, SpO2 saturation and pulse distention). All effects of MT-45 were compared with those of morphine. In vitro DMR assay results demonstrated that at human recombinant opioid receptors MT-45 behaves as a potent selective mu agonist with a slightly higher efficacy than morphine. In vivo results showed that MT-45 progressively induces tail elevation at the lowest dose tested (0.01 mg/kg), increased mechanical and thermal antinociception (starting from 1 to 6 mg/kg), decreased visual sensorimotor responses (starting from 3 to 6 mg/kg) and reduced tactile responses, modulated motor performance and induced muscle rigidity at higher doses (15 mg/kg). In addition, at higher doses (15–30 mg/kg) MT-45 impaired the cardiorespiratory functions. All effects were prevented by the administration of the opioid receptor antagonist naloxone. These findings reveal the risks associated with the ingestion of opioids and the importance of studying these drugs and undertaking more clinical studies of the current molecules to better understand possible therapeutic interventions in the case of toxicity. Highlights: MT-45 behaves as a potent selective mu agonist in DMR assay. MT-45 and morphine dose-dependently increased mechanical and thermal analgesia. MT-45 progressively impaired the motor-sensorimotor responses in mice as morphine. MT-45 altered cardiorespiratory responses in mice at higher doses.